Effects of a protocol for respiratory muscle training and balance in Guillain-Barré Syndrome: case report - Salete Wilk Wisniewski, Miriam; Dal’Maso Camera, Fernanda; Kempka Szczotka, Luciéle (Seven Editora, 2023)
Guillain-Barré Syndrome (GBS) is an inflammatory polyneuropathy, characterized by ascending demyelination of peripheral and cranial nerves. Respiratory and balance deficits and functional incapacity are expected limitations in these individuals. This study aimed to verify the effects of a respiratory and balance muscle training protocol in an individual with SBG. For this purpose, the following research instruments were used: Spirometry, Manovacuometry, Peak Expiratory Flow, Berg Balance Scale (BBS), and Functional Independence Measure (FIM). The respiratory training protocol was performed using Threshold IMT (30 – 50% MIP) and Threshold PEP (30% MEP). Balance training was divided into 3 phases, with progressive exercises and loads. Both protocols lasted four months, with three weekly interventions. As a result, it was observed that in the initial evaluation, there was inspiratory and expiratory weakness. After four months of intervention, MIP remained at the same value and MEP had an increase of 12.8% beyond the predicted value. Regarding the peak expiratory flow, in the evaluation, it was obtained at 75.31%, and in the reassessment 80.25% of the predicted value. Regarding the BBS in the evaluation, 50% of the total score was reached, and in the reevaluation, 89.28%. In the FIM assessment, initially 113 points, and in the reassessment 122 points. It is concluded that there was an improvement in the respiratory parameters, balance, and functional independence of the volunteer in this study, diagnosed with GBS. DOI: https://doi.org/10.56238/devopinterscie-181